THE PENGGUNAAN TEKNIK PENGELOMPOKKAN DALAM MENULIS TEKS DESKRIPTIF - Amalia Dinda Pratiwi; Ayu Istiana Sari (English Research Journal : Journal of Education, Language, Literature, Arts and Culture, 2023)
Abstract: The objective of this research was to find out whether the use of the Clustering Technique enhances the student’s ability in generating ideas. The subject of this research was 36 students of X.5 class at a public senior high school in Central Java 2022/2023 academic year. This research was categorized as Classroom Action Research (CAR) with two cycles. The writing test consisted of pre-test and post-tests to collect the data. The test was given to see how far the students enhanced their descriptive writing ability after the treatment. The data were analyzed by using a scoring rubric by Brown (2001). The result showed that the implementation of clustering technique can enhance the student’s ability to generate ideas in writing descriptive text. The mean score of students in the pre-test was 53.44, in post-test 1 was 56.67, and in post-test 2 was 74.305. There 88% of students (32 out of 36 students) who passed the Minimum Standard Score which is 70 in the or post-test 2. Keywords: Clustering Technique, Writing, Descriptive Text